Das Bild Luthers in der Literatur des 21. Jahrhunderts - Javor Briški, Marija (Vestnik za tuje jezike, 2018)
The paper focuses on the image of Martin Luther (1483-1546) in two novels of the 21st century: Waldtraut Lewin's Feuer. Der Luther-Roman (2014) and Richard Böck's Durchs Feuer hindurch. Ein Luther-Roman (2015). The analysis of the novels, that construct different images of Luther, is in consideration of the authors' intentions and target audience, and carried out on the narrative, thematic and motivic levels.
Keywords: 21.st.; Böck, Richard; imagologija; Lewin, Waldtraut; literarne študije; Luther, Martin; nemška književnost; nemški protestanti; nemški roman